Manifestation of strong magneto-electric dipolar coupling in ferromagnetic nanoparticles−FLC composite: evaluation of time-dependent memory effect. Issue 5 (9th April 2018) - Vimal, Tripti; Pandey, Shivani; Gupta, Swadesh K.; Singh, Dharmendra P.; Agrahari, Kaushlendra; Pathak, Govind; Kumar, Sumit; Tripathi, Pankaj K.; Manohar, Rajiv
ABSTRACT: Rod-shaped 5 wt.% copper-doped ZnO (ZnO:Cu 2+ ) ferromagnetic nanoparticles (NPs), prepared by hydrothermal method, were dispersed in ferroelectric liquid crystal (FLC) named Felix 17/100. The effect of ferromagnetic NPs on the physical properties of FLC material (Felix 17/100) has been investigated by dielectric, electro-optical and polarising optical microscopic methods. A noteworthy time-dependent memory has been observed in the NPs-dispersed FLC composite attributed to the coupling of magnetic field associated to NPs with the director orientation of FLC. Improvement in spontaneous polarisation and dielectric susceptibility of FLC material has been ensued with the addition of ferromagnetic NPs. Faster electro-optic response, at lower applied voltage, has also been observed in NPs-dispersed FLC composite. These changes are accredited to the magneto-electric dipolar coupling existing due to the interactions between magnetic-dipole and electric-dipole moments of magnetic NPs and FLC material, respectively. The formation of periodic domains capable to show memory effect has been observed in composite. The observed time-dependent memory was confirmed by dielectric and electro-optical methods. FLC material enriched with the properties of ferromagnetic NPs can be utilised in advanced multifunctional optical devices, time-dependent memory-based security devices and computational purposes. Graphical Abstract: